Pilot study on participation in outdoor recreation program determine perceived service quality in ecotourism services among tourists - Ab Aziz, Mohd Noorazlan; Aziz, Azlizam; Isa, Siti Suriawati (ISLAMIC WORLD Network for Environmental Science and Technology, 2015)
Background: Service quality has been an important topic in any business particularly in recreation experience within ecotourism services due to its intangible products. Outdoor recreation operators should look after their service quality because this will contribute to the future growth and development of tourism industry in Malaysia.Objective: To evaluate the effectiveness of ECOSERV model to determine perceived service quality among tourist while participated in outdoor recreation program. Results: Findings for overall alpha values were satisfactory as the alpha value is closer to the high reliability value. The six dimensions identified in the questionnaire showed medium to high reliability result, ranging from α=0.79 to α=0.94, which were consistent with the range of reliability in the original ECOSERV reliability test by Khan (2003). Conclusion: This ECOSERV instrument could be used and applicable as an assessment tool to evaluate the level of service quality in outdoor recreation programs toward outdoor recreation operators. This assessment would provide valuable information for service providers to upgrade the service quality based on the six dimensions in ECOSERV that most concerned by customer, participant or tourist.